Bacterial infection modulated by glucan: a search for the host defense potentiation mechanisms - Franĕk, J; Malina, J; Krátká, H (Folia microbiologica, 1992)
Interactions between bacteria and the host were studied from day 0 up to day 10 post-challenge in mice pretreated with soluble glucan (20 mg/kg i.p.) and challenged supralaryngeally with a virulent strain of Klebsiella pneumoniae. In the initial phase of infection, clearance of bacteria in the airways of glucan-treated mice was improved to an extent comparable with the vaccinated group but, in contrast to the immunized animals, subsequent regrowth of the bacterial inoculum was not prevented. The efficacy of defense, based during the entire course of infection mainly upon phagocytosis by neutrophils, markedly increased at intervals corresponding to the onset of humoral immune response. No evidence was obtained to indicate an enhanced involvement of alveolar macrophages in the phagocytosis of bacteria in glucan-stimulated mice. The results further support the notion that improvement of specific immune responsiveness rather than activation of nonspecific effector functions might be the most important expression of the host-defense-potentiating capacity of glucan and related stimulants of microbial origin.
Keywords: fluorescenční protilátková technika; Klebsiella pneumoniae; Lung; Klebsiella Infections; zvířata; myši; plíce; infekce bakteriemi rodu Klebsiella; Glucans; Mice; Mice, Inbred ICR; fagocytóza; Kinetics; Male; Spleen; Fluorescent Antibody Technique; glukany; Animals; myši inbrední ICR; mužské pohlaví; Phagocytosis; kinetika; slezina